2003
DOI: 10.2118/03-02-05
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results From a Solvent Gas Injection Field Test in a Depleted Heavy Oil Reservoir

Abstract: A field test was run during 1997 and 1998 to collect preliminary data on a solvent gas injection process. The site selected for the test was a "typical" Frog Lake, Alberta, Cummings formation reservoir that had been depleted using PC pump-based cold production methods on both 4 hectare (10 acre) and 8.1 hectare (20 acre) spacing. At the time of solvent injection, area average recovery from the test location was 9.5%, and the existence of wormholes in the reservoir was strongly suggested by regional well-to-wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Vapor extraction has been the subject of extensive experimental and numerical studies to investigate various aspects of this process. In addition to these laboratory studies, there are reported cases of field trials of solvent-aided processes in western Canada (Miller et al 2003;Gupta and Gittins, 2005). Despite relatively extensive literature on the vapor extraction process since 1989, the estimation of the efficiency of mass transfer phenomenon in porous media with characteristics of typical heavy oil reservoirs has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Vapor extraction has been the subject of extensive experimental and numerical studies to investigate various aspects of this process. In addition to these laboratory studies, there are reported cases of field trials of solvent-aided processes in western Canada (Miller et al 2003;Gupta and Gittins, 2005). Despite relatively extensive literature on the vapor extraction process since 1989, the estimation of the efficiency of mass transfer phenomenon in porous media with characteristics of typical heavy oil reservoirs has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Without considering the change in initial conditions provided by primary or secondary production techniques, the results of the studies only reflected the performance of solvent injection. However, it is expected that SVX processes will be used in the field as a post-cold production enhanced oil recovery method (1,8) . Generally the mechanisms of cold production are divided into two main categories: development of wormholes and foamy oil flow.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because the wormholed well allows the solvent to spread out over the reservoir more efficiently. However, in a real field situation, because of the complicated wormhole structure and possible thief zones, using the wormholed well as an injector may cause solvent loses outside the pattern area (Miller et al, 2003).…”
Section: Performance Of a Post-cold Production Svx Processmentioning
confidence: 99%
“…Without considering the change in initial conditions provided by primary or secondary production techniques, the results of the studies only reflected the performance of solvent injection. However, it is expected that SVX processes will be used in the field as a post-cold production enhanced oil recovery method (Miller et al, 2003;Knorr, 2006). Generally the mechanisms of cold production are divided into two main categories: development of wormholes and foamy oil flow.…”
Section: Introductionmentioning
confidence: 99%